THE EFFECT OF PROMOTIONAL MIX ON INTERNET ADOPTION IN JORDANIAN SMALL AND MEDIUM ENTERPRISES - Ghaith Mustafa Al-Abdallah; Azzam Azmi Abou-Moghli (European Scientific Journal, ESJ, 2012)
Internet is a new effective way to conduct business and marketing. It is used widely in the developed countries because of its unquestionable benefits especially for small and medium enterprises (SMEs) where internet provides great potential for such firms to compete world wild. SMEs are very important component of the national economies and are estimated to account for 80 percent of global economic growth. In developing countries, such as Jordan, internet adoption for marketing activities can be very helpful to SMEs. The main objective of this research is to examine the Promotional Mix effect on internet adoption in Jordanian SMEs, and highlight the actual use of internet in SMEs that adopted internet for marketing activities. One main and four sub- hypotheses were formed based on the literature review and previous studies. A restricted research methodology was used and those hypotheses were tested over a proportional systematic random sample obtained from the official records of Amman Chamber of Commerce for small and medium enterprises. Data was collected through questionnaires, 270 personally submitted questionnaires were distributed to the decisions makers in Jordanian SMEs. Statistical Package for the Social Science (SPSS) was chosen to describe and analyze the data of 253 filtered and screened questionnaires. The main result of this research showed that Promotional Mix has positive direct effect on internet adoption in Jordanian Small and Medium Enterprises; however this effect is weak as the statistical analysis revealed.